Contesting the presumption of paternity in Switzerland: a comparative perspective - Wudarski, Arkadiusz (Journal of the Belarusian State University. Law, 2023)
This paper is devoted to questions of contesting the presumption of paternity in Switzerland. The research covers both substantive and procedural issues, in particular the admissibility and the scope of the claim, the group of entitled persons, the time frame, the distribution of the burden of proof, and the consequences of lifting the presumption. Special attention is paid to the legal position of the biological father who is not the legal father. The analysis of Swiss law is accompanied by a Polish-German comparative legal perspective. The research leads to the conclusion that the mother’s marital status cannot absolutely determine the child’s affiliation. The legally imposed affiliation of the child, based on the principle of pater est quem nuptiae demonstrant, should be made more flexible. The biological father should have independent legal instruments to verify the child’s affiliation. In particular, he should be entitled to the challenge of paternity in the prenatal and postnatal periods. Finally, it is necessary to develop uniform and transparent criteria for questioning paternity, which will be created after carefully balancing all the opposing interests.
Keywords: presumption of paternity; new concepts of parenthood; legal status of biological father